ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO SKMART ASEMBAGUS - Ihsan, Anas Malik Fauzan Barqul; Subaida, Ida; Sari, Rini Kartika (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the factors that influence Consumer Satisfaction through Purchasing Decisions as an intervening variable at the SKMart Asembagus Store. The research method used is quantitative with a descriptive approach. The sample of this study amounted to 99 respondents selected by the probability sampling method. The data analysis technique used is structural equation analysis with the help of Smart PLS 3.0 software. The results of the study indicate that Product Diversity and Price have a significant positive effect on Purchasing Decisions, while Service Quality has a significant positive effect on Purchasing Decisions, in addition, Product Diversity has a positive but insignificant effect on Consumer Satisfaction, while Price has a positive but insignificant effect on Consumer Satisfaction, and Service Quality has a significant positive effect on Consumer Satisfaction. Purchasing decisions are proven to have a positive but insignificant effect on Consumer Satisfaction. Indirectly, Product Diversity and Price have a positive but insignificant effect on Consumer Satisfaction through Purchasing Decisions, while Service Quality has a positive but insignificant effect on Consumer Satisfaction through Purchasing Decisions.